2022
DOI: 10.1001/jamasurg.2022.2230
|View full text |Cite
|
Sign up to set email alerts
|

Extended Focal Ablation of Localized Prostate Cancer With High-Frequency Irreversible Electroporation

Abstract: IMPORTANCEFocal therapy of prostate cancer must balance the oncologic outcome and functional outcome. High-frequency irreversible electroporation (H-FIRE) can destroy cancer cells while selectively preserving surrounding nerves and blood vessels, but no clinical trials have been conducted, to our knowledge. OBJECTIVE To evaluate the efficacy and safety of H-FIRE in the treatment of localized prostate cancer (PCa). DESIGN, SETTING, AND PARTICIPANTS This was a single-group, objective performance criteria, nonran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 33 publications
0
15
0
1
Order By: Relevance
“…We believe the data presented by Wang et al are reasonable in demonstrating histologic efficacy of the ablation technique they studied. Nonetheless, the broader clinical questions essential to establish focal therapy for prostate cancer remain unanswered—namely in whom is this therapy oncologically effective and how should we define oncologic efficacy?…”
mentioning
confidence: 57%
See 1 more Smart Citation
“…We believe the data presented by Wang et al are reasonable in demonstrating histologic efficacy of the ablation technique they studied. Nonetheless, the broader clinical questions essential to establish focal therapy for prostate cancer remain unanswered—namely in whom is this therapy oncologically effective and how should we define oncologic efficacy?…”
mentioning
confidence: 57%
“…Wang et al provide histologic efficacy data for an energy modality for the focal treatment for localized prostate cancer . The study offers a promising proof of concept in the continuing development and refinement of techniques for focal treatment in prostate cancer.…”
mentioning
confidence: 99%
“…Pathological analysis showed that there was no viable prostate cancer within the ablation zone, which had been replaced by tissue necrosis and inflammatory response [48] Clavien-Dindo Grade III-IV adverse event observed. A risk of recurrence or residual tumor of 3% at 6 months and 2.7% at 12-months was demonstrated [49,50]. Disease-free survival, defined as avoidance of whole gland therapy or metastasis/death related to prostate cancer was 96.75% at 3 years [49].…”
Section: Prostate Cancermentioning
confidence: 99%
“…IRE is the permeabilization of cell membranes with electrical pulses, which affect membranous electrochemical potentials, creating pores in a lipid bilayer [ 238 ]. IRE has been already used in PC management, both as a focal therapy, and as the whole gland ablation [ 239 , 240 , 241 , 242 , 243 , 244 , 245 , 246 ]. The procedure is based on needle electrodes, which are placed inside or nearby the targeted tissue.…”
Section: Focal Ablation and Immune Therapy Combinationmentioning
confidence: 99%